2015
DOI: 10.1021/acs.analchem.5b03570
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide with Different Crystal Phases (α- and γ-Fe2O3) in Electroanalysis and Ultrasensitive and Selective Detection of Lead(II): An Advancing Approach Using XPS and EXAFS

Abstract: Iron oxide with different crystal phases (α- and γ-Fe2O3) has been applied to electrode coatings and been demonstrated to ultrasensitive and selective electrochemical sensing toward heavy metal ions (e.g., Pb(II)). A range of Pb(II) contents in micromoles (0.1 to 1.0 μM) at α-Fe2O3 nanoflowers with a sensitivity of 137.23 μA μM(-1) cm(-2) and nanomoles (from 0.1 to 1.0 nM) at γ-Fe2O3 nanoflowers with a sensitivity of 197.82 μA nM(-1) cm(-2) have been investigated. Furthermore, an extended X-ray absorption fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(58 citation statements)
references
References 57 publications
5
53
0
Order By: Relevance
“…The intensity of the peak corresponding to the surface oxygen was significantly higher for γ as compared to α-Fe 2 O 3 that depicted the higher tendency of γ-Fe 2 O 3 towards surface O-H formation. The observation was in compliance with that reported earlier[61,62]. The deconvoluted, fitted Fe 2p peaks of both the polymorphs are compared inFig.…”
supporting
confidence: 90%
“…The intensity of the peak corresponding to the surface oxygen was significantly higher for γ as compared to α-Fe 2 O 3 that depicted the higher tendency of γ-Fe 2 O 3 towards surface O-H formation. The observation was in compliance with that reported earlier[61,62]. The deconvoluted, fitted Fe 2p peaks of both the polymorphs are compared inFig.…”
supporting
confidence: 90%
“…In these studies, iron oxide almost presents in α-Fe 2 O 3 [15,21,26] or Fe 3 O 4 [25] crystal phase in the as-prepared catalysts. Considering that γ-Fe 2 O 3 is one kind of iron oxide as common as α-Fe 2 O 3 [27,28], it is surprising that there are very few reports about the behavior of γ-Fe 2 O 3 in CO 2 hydrogenation. Al-Dossary et al found γ-Fe 2 O 3 coexisted with α-Fe 2 O 3 in the catalysts, but no benefit from γ-Fe 2 O 3 was disclosed [21].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Dossary et al found γ-Fe 2 O 3 coexisted with α-Fe 2 O 3 in the catalysts, but no benefit from γ-Fe 2 O 3 was disclosed [21]. However, it has been confirmed that γ-Fe 2 O 3 is superior to α-Fe 2 O 3 in other catalytic reactions, such as photodecomposition of H 2 S [29], selective catalytic reduction of NO X with NH 3 [30], electroanalysis and ultrasensitive detection of Pb 2+ [27], WGS reaction [31] and so on. The lack on the performance of γ-Fe 2 O 3 in CO 2 hydrogenation makes it necessary to study Fe catalyst in γ-Fe 2 O 3 phase, not only to supply the knowledge about γ-Fe 2 O 3 in the reaction, but also to find active catalyst to make CO 2 profitable.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption-release model is often used to describe the stripping voltammetric technique [35]. Scheme 1 illuminates how adsorption-release process affects the heavy metal ions sensing on the TiO2 (001) and (101) facets.…”
Section: Optimal Exposed Facet Suggested By Dft Calculationmentioning
confidence: 99%